2023
DOI: 10.3390/molecules28104064
|View full text |Cite
|
Sign up to set email alerts
|

UPLC-QE-Orbitrap-Based Cell Metabolomics and Network Pharmacology to Reveal the Mechanism of N-Benzylhexadecanamide Isolated from Maca (Lepidium meyenii Walp.) against Testicular Dysfunction

Kai-Yue Zhang,
Chun-Nan Li,
Nan-Xi Zhang
et al.

Abstract: Testicular dysfunction (TDF) is characterized by testosterone deficiency and is caused by oxidative stress injury in Leydig cells. A natural fatty amide named N-benzylhexadecanamide (NBH), derived from cruciferous maca, has been shown to promote testosterone production. Our study aims to reveal the anti-TDF effect of NBH and explore its potential mechanism in vitro. This study examined the effects of H2O2 on cell viability and testosterone levels in mouse Leydig cells (TM3) under oxidative stress. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The unstable sulfated compound leads to isothiocyanate formation by the Sulfotransferase (SOT) and Glucosyltransferasa (UGT74) (Blažević et al, 2020). (B) The enzymolysis of the benzylglucosinolate the generation of benzylamine is accomplished by ( Zhang et al, 2023 ). (C) In this example Linoleic acid serves as the scaffold for the formation of 9-hydroperoxy-10E,12Z-octadecadienoic acid and 13-hydroperoxy-9Z,12E-octadecadienoic acid through lipoxygenase enzymes, and then transfers the fundamental skeleton of macaenes using 9 or 13-hydroperoxy-10E,12Z-octadecadienoic acid.…”
Section: Phytochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The unstable sulfated compound leads to isothiocyanate formation by the Sulfotransferase (SOT) and Glucosyltransferasa (UGT74) (Blažević et al, 2020). (B) The enzymolysis of the benzylglucosinolate the generation of benzylamine is accomplished by ( Zhang et al, 2023 ). (C) In this example Linoleic acid serves as the scaffold for the formation of 9-hydroperoxy-10E,12Z-octadecadienoic acid and 13-hydroperoxy-9Z,12E-octadecadienoic acid through lipoxygenase enzymes, and then transfers the fundamental skeleton of macaenes using 9 or 13-hydroperoxy-10E,12Z-octadecadienoic acid.…”
Section: Phytochemistrymentioning
confidence: 99%
“…Network Pharmacology and in silico docking revealed that part of the mechanism of N-Benzylhexadecanamide (NBH). This molecule directly binds and inhibit the CYP1A2 (Cytochrome P450 Family 1 Subfamily A Member 2) active center, which in turn reduces the production of 16α-hydroxydehydro epiandrosterone, preventing excessive consumption of the testosterone (T) precursor DHEA and making it available for T synthesis ( Zang et al, 2023 ).…”
Section: Phytochemistrymentioning
confidence: 99%
“…Newer research on the science of maca phytochemicals continues, with some recent publications looking at the immunomodulatory [ 98 ] and neuroprotective [ 129 ] aspects of polysaccharides from maca, along with testing isolated compounds like a natural fatty amide known as N -benzylhexadecanamide for its ability to enhance testosterone production [ 130 ]. Using proteomics and lipomics methods, the neuroprotective effects imparted by N -benzylhexadecanamide may be attributed to its effects on sphingolipid metabolism and mitochondrial function, suggesting that it could continue to be investigated for neurodegenerative diseases [ 131 ].…”
Section: Select Maca Phytochemicalsmentioning
confidence: 99%
“…6 Consequently, this approach unveils the metabolic pathways and processes of the relevant cells, rendering it highly valuable for in vitro investigations concerning alterations in metabolic profiles and the underlying mechanisms induced by pharmaceutical interventions. 7 In comparison to comprehensive metabolic investigations, cellular metabolomics offers distinct advantages, including the ability to easily regulate experimental variables, achieve high reproducibility, incur low costs, and facilitate result interpretation. Zebrafish (Danio rerio) possesses exceptional attributes such as its diminutive size, prolific reproduction, economical upkeep, brief experimental duration, and substantial homology with mammals, particularly humans.…”
Section: Introductionmentioning
confidence: 99%